Tinjauan Hukum Islam Terhadap Bagi Hasil Tambak Ikan - Dimas Yusuf Ermiza; Darul Muftadin; Satria Budiman (el hisbah: Journal of Islamic Economic Law, 2022)
This article was motivated by the existence of a capital goods financing product using an ijarah Muntiyah Bittamlik contract at KSPPS BTM Pekalongan. The financing product is a form of product innovation that aims to meet the needs of the community. The objectives of the research are: 1) to know the mechanism of implementing the ijarah Muntiyah bittamlik contract on capital goods financing products; and 2) analyzing the application of the DSN-MUI Fatwa Number 27/DSN-MUI/III/2002 on capital goods financing products. This research is an empirical legal research using a qualitative approach. Primary data sources are obtained from interviews with related parties, such as employees, customers, and the Sharia Supervisory Board. Meanwhile, secondary data sources are obtained from literature studies, such as books and journals that are relevant to the research issue. The results show that, the transfer of ownership rights to goods begins with the rental of objects/goods to customers within a certain period of time with a rental payment system, followed by the transfer of ownership rights to objects through grants to customers.